A comparison of fit, heat stress, oxygen saturation and comfort between a novel reusable mask and disposable N95 respirator - Maddison Strickling; Nasheed Zarif; Hoang Nguyen; Samira Moradi Khalaj; C Raina MacIntyre; Robert Packard; Guna Selvaduray; Yun Wang (PLoS ONE, 2025)
The effectiveness of face masks in infection prevention depends not only on filtration technology but also on user compliance. However, existing masks suffer from limitations impacting comfort, ease of use, and communication, leading to reduced compliance, especially during prolonged use in healthcare settings. Innovations in mask design are needed to address these issues to ensure effective protection. To provide insights into novel face mask design aimed at enhancing infection prevention in healthcare settings and to introduce new evaluation methods for novel face masks, a fit and usability study was conducted with 22 volunteers, comparing a novel reusable mask, Altus Hero 1 (Hero), to N95 respirators. Subjects performed Occupational Safety and Health Administration (OSHA)-accepted quantitative fit test and usability test, and completed a post-test survey. The survey assessed communication, breathability, humidity retention, eyeglasses fitting, and long-term wear preference. Face temperature and blood oxygen levels were recorded during testing. Hero showed significantly reduced heat retention (p<0.05) compared to N95, aligning with survey responses indicating Hero felt cooler. No significant differences were found in blood oxygen levels between masks. Despite needing design refinements, most subjects preferred Hero for comfort and usability. This study discusses enhancements in design, fit, comfort, and materials to better meet users’ needs and ensure compliance. It highlights critical and universal design considerations for future face masks and introduces methodological innovations for evaluating mask fit and usability. The findings offer valuable insights for advancing personal protective equipment for preventing infections and future pandemics.